Geographic variation and associated factors of long-acting contraceptive use among reproductive-age women in Ethiopia: a multi-level and spatial analysis of Ethiopian Demographic and Health Survey 2016 data - Oumer Abdulkadir Ebrahim; Ejigu Gebeye Zeleke; Atalay Goshu Muluneh (BMC, 2021)
Plain language summary Lower and middle-income countries such as Ethiopia face a challenge of an ever increasing population with high maternal mortality. In Ethiopia, the population is estimated to be more than 110 million. High fertility rates, unintended pregnancy, maternal and child mortalities are the main concerns of the country. Accordingly, it is required of the country to make a robust intervention to limit these public concerns. In relation to this, LACs utilization happens to be one of the solutions to solving the concerns. Despite their efficacy, availability, and acceptability the utilization of LACs remains low and varies among different geographic areas. However, the reason is still undefined and geographic variation was not assessed before. In our study, we analyze the Ethiopian demographic and health survey 2016 data to assess the presence of significant geographic variation and associated factors of long-acting contraceptive utilization. Hence, a spatial and multilevel analysis were employed to assess the geographic variation and associated factors of LACs utilization in Ethiopia. A statistically significant geographic variation was observed among different clusters. Clusters with significantly low utilization of LACs were found in the pastoralist (Afar, Gambela, and Somalia) regions of the country. Thus, more organized efforts need to be made to increase the utilization of LACs. Controlling for others: Marital statuses, occupation, future pregnancy interest, urban residence, previous history of abortion, living in the pastoralist community were statistically significant determinant factors of LACs utilization. In conclusion, significant geographic variation of LACs utilization was observed among different clusters. Besides, different socio-demographic, pregnancy, and child health-related variables were significant determinants of LACs utilization.